2020
DOI: 10.4103/ijem.ijem_305_19
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-Müllerian hormone in polycystic ovary syndrome and its relationship with insulin resistance, lipid profile and adiponectin

Abstract: Objectives: This study was done to estimate serum anti-Müllerian hormone (AMH) level in polycystic ovary syndrome (PCOS) patients and to correlate serum AMH level with insulin resistance, lipid profile, and adiponectin levels. Materials and Methods: A cross-sectional study was conducted at Hospital Universiti Sains Malaysia (Hospital USM), Health Campus, Kubang Kerian, Kelantan, Malaysia. Thirty newly diagnosed patients with PCOS attending gynecology clinic between July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“… 26 , 27 A significant negative correlation between serum AMH and insulin resistance had been observed in PCOS women. 28 , 29 Abdolhian et al 30 showed that an exercise intervention can significantly decrease AMH levels. AMH levels in PCOS cases could be regulated by a complicated mechanism, because PCOS is a complex reproductive and hormonal disorder that can derange metabolic parameters.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 A significant negative correlation between serum AMH and insulin resistance had been observed in PCOS women. 28 , 29 Abdolhian et al 30 showed that an exercise intervention can significantly decrease AMH levels. AMH levels in PCOS cases could be regulated by a complicated mechanism, because PCOS is a complex reproductive and hormonal disorder that can derange metabolic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that there was a significant negative correlation between AMH level and homeostasis model assessment of insulin resistance (HOMA-IR) or triglyceride levels, and a positive correlation between AMH and high-density lipoprotein cholesterol (HDL-C) or serum adiponectin level, so that AMH is also a potential cardiometabolic risk marker in women with PCOS. 28 Although the correlation between AMH and BMI remains unclear, the associations between AMH and metabolic syndrome were modified by BMI; hence, the women who had PCOS with normal BMI did not have an increased risk of metabolic syndrome. 29 The present study is a retrospective study, and owing to the mobility of outpatients and incomplete data, metabolic markers were not included in the clinical data and the corresponding causal analysis data could not be obtained from this study; we will confirm these data in subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of androgen can regulate menstrual cycle, but ovulation cannot be restored during treatment. 8 At the same time, once the drug is stopped, menstrual disorder will return, with no long-term treatment effect. Metformin, which can improve insulin resistance, has been proved to be an adjuvant therapy for ovulation induction and androgen reduction, but cannot completely regulate the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%